Capsaicin-sensitive vagal fibres and 5-HT3-, gastrin releasing peptide- and cholecystokinin A-receptors are involved in distension-induced inhibition of gastric emptying in the rat - YEGEN, BERRAK (My University, 1999)
The present study was undertaken to investigate how the activation of gastric mechanoreceptors by distension of the stomach in conscious gastric fistula rats influences gastric emptying; and the roles of capsaicin sensitive vagal afferent fibres and the 5-HT3, GRP and CCK-A receptors involved in mediating these responses. To activate mechanoreceptors by non-nutrient dependent pathways, methylcellulose in saline was used to distend the stomach (5 cm H2O) and the subsequent emptying of saline was examined immediately, and at 3, 5 and 10 min following distension. Prior distension delayed the subsequent emptying of saline instilled into the stomach compared with non-distended controls (2.28+/-0.09 ml/5 min; P < 0.001). Topical application of capsaicin, completely abolished the distension-induced inhibition of gastric emptying when compared with vehicle treated rats (2.82+/-0.09 vs. 2.38+/-0.04 ml/5 min; P < 0.001). Peripheral administration of a GRP antagonist (2258 U89UJ, 1 mg/kg), and a 5-HT3 antagonist (BRL4369UA, 50 microg/kg) significantly reversed (2.56+/-0.14 ml/5 min; P < 0.05 and 2.61+/-0.07 ml/5 min; P < 0.01; respectively) the delay in gastric emptying induced by distension. When the rats were treated with the CCK-A antagonist, gastric emptying of saline following distension was also significantly facilitated (2.56+/-0.07 ml/5 min; P < 0.001). In contrast, the CCK-B/gastrin receptor antagonist had no significant effect on the distension induced delay in gastric emptying (1.95+/-0.12 ml/5 min). The present results suggest that gastric distension in conscious gastric fistula rats delays gastric emptying by activating capsaicin-sensitive extrinsic afferent nerve fibres. Moreover, the results also indicate that distension-induced mechanisms involve GRP, 5-HT3 and CCK-A receptors, but not CCK-B receptors.
Keywords: Animals; Male; Rats; Oligopeptides; Rats, Sprague-Dawley; Capsaicin; Gastric Emptying; Stomach; Vagus Nerve; Receptors, Serotonin; Serotonin Antagonists; Granisetron; Receptor, Cholecystokinin A; Receptors, Bombesin; Receptors, Cholecystokinin; Receptors, Serotonin, 5-HT3